Systematic review of the differences between mothers and fathers in parenting styles and practices - Yaffe, Yosi (Current psychology (New Brunswick, N.J.), 2023)
Parenting is a broad construct that comprises stable and durable attitudes and behaviors regarding child-rearing. Since mothers and fathers play different roles in the family, parenting styles and practices in childhood and adolescence may differ depending on the parents’ and adolescents’ gender. While gender differences in parenting are theoretically warranted, the research literature in this field is considerably limited and lacking conclusive information dealing with this question. Therefore, the aim of this systematic review is to aggregate and synthesize the available research studies containing significant findings on the differences between mothers and fathers in parenting styles and practices. For that purpose, we conducted a systematic search of the PsycInfo, Scopus, Eric, and Web of Science databases, covering literature published from 1990 to 2020. The search was restricted to peer-reviewed studies in English alone. Our findings reveal that mothers as compared to fathers are perceived as more accepting, responsive, and supportive, as well as more behaviorally controlling, demanding, and autonomy granting than fathers. Accordingly, in the studies comparing parents on the constructs of overall parenting styles, mothers were predominantly more authoritative than fathers, and fathers were mostly more authoritarian than mothers (based on both parent and descendant reports). These parental differences established by research from over 15 countries around the globe seem to apply similarly for male and female descendants, while principally not varying by their age.